LEAD AND STRONTIUM ISOTOPES AS MONITORS OF EXPERIMENTAL GRANITOID MINERAL DISSOLUTION - Erel Y.; Blum J.D.; Roueff E.; Ganor J. (My University, 2004)
Flow-through dissolution experiments were carried out on crushed granitoid rock (the Elat Granite) and three mineral separates (plagioclase, perthite, and biotite + chlorite) from this rock at pH 1 and 25°C. Major element concentrations were combined with Pb and Sr isotopic analyses of starting materials and output solutions and together enabled us to elucidate several important mechanisms related to granitoid rock weathering. We observed an initial stage of rock dissolution (